Chitosan as a Postharvest Alternative for the Control of Phytophthora capsici in Bell Pepper Fruits - Juan Antonio Torres-Rodriguez; Juan José Reyes Pérez; Luis Tarquino Llerena Ramos; Leonardo Gonzalo-Matute; Edgar Omar Rueda-Puente; Luis Guillermo Hernandez-Montiel (Sci)
Phytophthora capsici is a phytopathogen that affects postharvest bell peppers, as it causes rotting and decreases their commercial value. This study evaluates the efficacy of chitosan as a biocontrol agent against P. capsici on bell peppers using in vitro and in vivo assays. The antifungal activity of chitosan was evaluated at four concentrations (0.5, 1.0, 1.5, and 2.0 g L−1). Its effect on mycelial growth inhibition, sporangial germination, disease incidence and severity, and fruit weight loss was determined. The results show that concentrations of 1.0 g L−1 or higher completely inhibited P. capsici growth and sporangial germination in vitro and reduced disease incidence and severity to 0% in treated fruit. Furthermore, chitosan treatments preserved the fresh and dry weight of the fruit, which prevented postharvest deterioration. This study demonstrates that chitosan is an effective and environmentally friendly alternative for the management of postharvest diseases in bell peppers. This could reduce consumer dependence on synthetic fungicides and preserve fruit quality.